Nonparametric quantile regression for twice censored data - Dette, Holger; Volgushev, Stanislav (Technische Universität Dortmund, 2009)
We consider the problem of nonparametric quantile regression for twice censored data. Two new estimates are presented, which are constructed by applying concepts of monotone rearrangements to estimates of the conditional distribution function. The proposed methods avoid the problem of crossing quantile curves. Weak uniform consistency and weak convergence is established for both estimates and their finite sample properties are investigated by means of a simulation study. As a by-product, we obtain a new result regarding the weak convergence of the Beran estimator for right censored data on the maximal possible domain, which is of its own interest.
Discussion Paper / SFB 823; 23/2009
Keywords: Beran estimator; censored data; crossing quantile curves; monotone rearrangements; quantile regression; survival analysis; 310; 330; 620